Variation across a wheat genetic diversity panel for saccharification of hydrothermally pretreated straw - Samuel R. A. Collins; David R. Wilson; Graham K. Moates; Andrea L. Harper; Ian Bancroft; Keith W. Waldron (Biotechnology for Biofuels, 2017)
Abstract Background Wheat straw forms an important, reliable source of lignocellulosic biomass for use in second-generation ethanol production. However, there is limited understanding of the variation in quality of straw from current breeding cultivars, and studies on such variation have generally employed suboptimal pretreatments. There is also a degree of confusion regarding phenotypic characteristics relevant to optimising the enzymatic saccharification of cellulose after suitable pretreatments for biorefining compared with those which determine good ruminant digestibility. The aim of this study has been to (a) evaluate and compare the levels of glucose enzymatically released from straw obtained from 89 cultivars of winter wheat after optimised hydrothermal pretreatments and (b) identify the underlying phenotypic characteristics relevant to enhanced glucose production with special reference to the ratios of constituent tissue types. Results Optimised pretreatment involved hydrothermal extraction at 210 °C for 10 min. Using excess cellulases, quantitative saccharification was achieved within 24 h. The amount of glucose released ranged from 192 to 275 mg/g. The extent of glucose release was correlated with (a) the level of internode tissue (R = 0.498; p = 6.84 × 10−7), (b) stem height (R = 0.491; p = 1.03 × 10−6), and (c) chemical characteristics particular to stem tissues including higher levels of cellulose (R = 0.552; p = 2.06 × 10−8) and higher levels of lignin R = 0.494; p = 8.67 × 10−7. Conclusions In order to achieve maximum yields of cellulosic glucose for second-generation ethanol production, a predisposition for wheat to produce cellulose-enriched internode stem tissue, particularly of longer length, would be beneficial. This contrasts with the ideotype for ruminant nutrition, in which an increased proportion of leaf tissue is preferable.